Pengaruh POC Kitosan Cangkang Rajungan (Portunus pelagicus) Terhadap Pertumbuhan Jagung Gigi Kuda (Zea mays sindetat) - Sahubauwa, Laila; Mau, Emilia; Mutmainnah, Heni (INSTITUT AGAMA ISLAM NEGERI AMBON, 2025)
Crab shell waste can be used as raw material for making chitosan. Chitosan is the result of chitin degassing which has many benefits, including in agriculture. Chitosan has been proven to increase plant growth. In the agricultural industry, chitosan can be used as POC. This study aims to determine the effect of POC chitosan from crab shells (P. Pelagicus) on the growth of horsetooth corn (Z. mays syndetat). The type of quantitative research with a field experiment approach using 1% chitosan POC treatment from male, female and mixed male and female crab shells, as much as 20 ml of 1% chitosan/1 liter of water. The indicators observed were plant height, stem diameter and number of leaves. Using RAK (completely randomized design) with Anova analysis (one way) assisted by SPSS version 20. The results showed that POC chitosan from male, female and mixed crab shells had an effect (sig <0.05) on plant height, stem diameter and number of leaves. The best effect was shown by mixed chitosan POC on plant height (89.00 cm), male chitosan POC on stem diameter (15.61 mm) and male, female, mixed chitosan POC on the number of leaves (10.00 strands). Keywords: Chitosan POC, Crab Shell Waste, Horse Tooth Corn